Faktor-Faktor yang Mempengaruhi Kepuasan Kerja Karyawan di PT. Intrias Mandiri Sejati (IMS) - Abdul Madjid; Tantri Widiastuti (STIE Widya Manggala, 2013)
Reliable human resources owned by the company provides a distinct advantage. The aim of this research was to determine the influence of individual factor, social factor and main factor in work at outsourcing employee of Collection Division of PT. Intrias mandiri Sejati ( IMS ) which is placed at PT. Bank Internasional Indonesia branch Majamas Semarang. The population used as well the samples in this research were 50 employees with purposive sampling. The analysis tool used in this research was multiple linear regresssion, which was previously tested by validity and reliability to see the data quality. The results showed that the individual factor, the social factor and the main factor in work influenced the employee’s job satisfaction at outsourcing employee of Collection Division of PT. Intrias mandiri Sejati ( IMS ) which is placed at PT. Bank Internasional Indonesia branch Majamas Semarang.